1999
DOI: 10.1017/s0025315498000101
|View full text |Cite
|
Sign up to set email alerts
|

Larval development of the intertidal barnacles Chthamalus stellatus and Chthamalus montagui

Abstract: Two recently-distinguished species of Chthamalus (Cirripedia) are found on rocky shores in the northeastern Atlantic: C. stellatus predominant on islands and headlands and C. montagui more abundant in bays. Larvae of the two species were produced in laboratory cultures to describe and compare the morphology and to allow identi¢cation in plankton samples. Nauplius larvae of C. stellatus are up to 30% larger than those of C. montagui. Di¡erences in setation are minor. The two species are easily distinguishable f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
1
6

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 34 publications
2
39
1
6
Order By: Relevance
“…Chthamalus stellatus and C. montagui, under experimental conditions, took approximately 17 d to reach the cyprid stage (Burrows et al 1999), but there is no information about the time taken for their body reserves to become so depleted that they would be un-able to metamorphose. As an indication, it is reported that at 10°C, cyprids of Balanus balanoides can survive for between 2.5 and 4 wk and still metamorphose (Lucas et al 1979).…”
Section: Discussionmentioning
confidence: 99%
“…Chthamalus stellatus and C. montagui, under experimental conditions, took approximately 17 d to reach the cyprid stage (Burrows et al 1999), but there is no information about the time taken for their body reserves to become so depleted that they would be un-able to metamorphose. As an indication, it is reported that at 10°C, cyprids of Balanus balanoides can survive for between 2.5 and 4 wk and still metamorphose (Lucas et al 1979).…”
Section: Discussionmentioning
confidence: 99%
“…For larval classification the following descriptions were used: Norris & Crisp (1953) for Balanus perforatus, Pyefinch (1948) for B. crenatus, Burrows et al (1999) for Chthamalus montagui and C. stellatus, and Bassindale (1936) and Pyefinch (1948) for Verruca stroemia. In estimating larval release we counted Nauplius I and II stages.…”
Section: Methodsmentioning
confidence: 99%
“…The processes controlling the distribution patterns of C , stellatus and C. montagui are as yet unknown. There are some differences between the 2 species in settled cyprid density relative to metan~orph abundance ) and larval development time (Burrows et al 1999). Studies which compare sympatric larval settlement in the field between these species have been hampered because, although minute structural differences in the cyprid carapace have been reported in C. stellatus and C. montagui (Jensen et al 1994), no diagnostic tool for species identification as cyprids has been available.…”
Section: Introductionmentioning
confidence: 99%
“…Carapace length has been suggested as a method of distinguishing between larvae of Chthamalus stellatus and C, montagui from field samples (Burrows 1988, Burrows et al 1999). The present work investigated size as a useful means of identifying C. stellatus and C. montagui cyprids from field samples collected at different dates in south and west Ireland.…”
Section: Introductionmentioning
confidence: 99%